2021
DOI: 10.17219/acem/141604
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status in Polish women with endocrine and osteoporotic disorders in relation to diet, supplement use and exposure to ultraviolet radiation

Abstract: Background. In Europe, the rate of 25(OH)D deficiency is considered high. Thus, it seems necessary to conduct population-based studies to fully assess vitamin D deficiency in various groups of patients.Objectives. To evaluate serum 25(OH)D levels and the frequency of deficiency in women in Poland with endocrine and osteoporotic disorders. The influences of diet, use of vitamin/mineral supplementation and exposure to ultraviolet (UVB) radiation on vitamin D status in women with metabolic disorders were also exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In addition to that, the most crucial factors influencing vitamin D status in Polish women with endocrine and osteoporotic disorders, were mainly regular fish consumption, spending holidays in sunny destinations, and regular intake of vitamin D preparations [ 158 ]. In another sample of young Polish women, aged 15–30 years, herring, sardine, and tuna products were amongst the food sources where highest vitamin D intake was observed, with a strong correlation between total vitamin D intake and its intake from these fish sources, while the correlation between total vitamin D intake and the number of servings was strongest for herring, sardine, and tuna products, in comparison to all the other food sources [ 159 ].…”
Section: Fish Lipid Bioactives and Health Benefitsmentioning
confidence: 99%
“…In addition to that, the most crucial factors influencing vitamin D status in Polish women with endocrine and osteoporotic disorders, were mainly regular fish consumption, spending holidays in sunny destinations, and regular intake of vitamin D preparations [ 158 ]. In another sample of young Polish women, aged 15–30 years, herring, sardine, and tuna products were amongst the food sources where highest vitamin D intake was observed, with a strong correlation between total vitamin D intake and its intake from these fish sources, while the correlation between total vitamin D intake and the number of servings was strongest for herring, sardine, and tuna products, in comparison to all the other food sources [ 159 ].…”
Section: Fish Lipid Bioactives and Health Benefitsmentioning
confidence: 99%
“…These studies may have inspired individuals to take dietary supplements, but they should always be taken as prescribed and in the recommended dosages [6]. Unbalanced eating habits have been linked to decreased vitamins and minerals levels, which can have a negative impact on the body's metabolic processes and contribute to various illnesses such as pellagra, rickets, scurvy, beriberi, osteoporosis, and other vitamin deficiencies [7]. Dietary supplements are presently utilized more frequently than ever before due to their efficacy and safety in improving general health [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…For example, they tend to consume more animal fat and alcohol, while consuming less grains, fresh vegetables, and beans [ 15 ]. Studies have shown that unbalanced eating habits decrease the level of vitamins and minerals, which are insufficient for maintaining the body's normal functions, and eventually cause scurvy, beriberi, pellagra, rickets, osteoporosis, and other vitamin deficiencies [ 16 , 17 ]. In a survey of adult residents in the United States, about 23% of DS consumers were advised by health care professionals to improve their physical condition and maintain their health [ 18 ].…”
Section: Introductionmentioning
confidence: 99%